A highly concentrated phosphate-based electrolyte for high-safety rechargeable lithium batteries. Issue 35 (13th April 2018) - Shi, Pengcheng; Zheng, Hao; Liang, Xin; Sun, Yi; Cheng, Sheng; Chen, Chunhua; Xiang, Hongfa
Abstract : A highly concentrated phosphate-based electrolyte with nonflammable and dendrite-suppressing properties enables safe rechargeable lithium batteries. Abstract : We prepare a totally nonflammable phosphate-based electrolyte composed of 5 mol L −1 (M) Li bis(fluorosulfonyl) imide (LiFSI) in a trimethyl phosphate (TMP) solvent. The concentrated 5 M LiFSI/TMP electrolyte shows good compatibility with graphite and no Al corrosion. More attractively, such a concentrated electrolyte can effectively suppress the growth of Li dendrites in Li metal batteries because of a stable LiF-rich SEI layer. Therefore, this highly concentrated electrolyte is promising for safe Li batteries.